2014
DOI: 10.3171/2014.7.jns132037
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological outcome after epilepsy surgery in patients with bilateral Ammon's horn sclerosis

Abstract: Object. The purpose of this study was to retrospectively assess the objective and subjective neuropsychological outcome after epilepsy surgery in patients with bilateral Ammon's horn sclerosis (AHS).Methods. Memory and executive functions were evaluated at baseline and at follow-up in 11 surgically treated patients and compared with 8 pharmacologically treated patients with temporal lobe epilepsy and bilateral AHS. The median follow-up duration was 16 months in the surgically treated patients and 80.5 months i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
2
8
0
1
Order By: Relevance
“…Previous studies also showed similar results in other centers. 11,38,39 Our study similarly showed a good outcome regarding seizure control for the BHS group with 5.50 years (SD 2.92) of follow-up duration after a carefully planned resection.…”
Section: Prognosis and Results Of Epilepsy Surgerysupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies also showed similar results in other centers. 11,38,39 Our study similarly showed a good outcome regarding seizure control for the BHS group with 5.50 years (SD 2.92) of follow-up duration after a carefully planned resection.…”
Section: Prognosis and Results Of Epilepsy Surgerysupporting
confidence: 79%
“…5,[8][9][10][11]22 We showed that history of FSE, mental retardation, status epilepticus, psychosis, slowing of the EEG background activity were significant clues for BHS patients in comparison to UHS group.…”
Section: Discussionmentioning
confidence: 92%
“…Although the previously published surgical case series have reported good seizure outcomes, unilateral resection in patients with bilateral HS, even if the patient is rendered seizure‐free, can compromise remaining memory function . Moreover, ambulatory electrocorticography recorded from NeuroPace responsive neurostimulation devices has now shown that seizures may arise for several weeks in one hippocampus before then switching to the other .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in this cohort, very few patients ( Although the previously published surgical case series have reported good seizure outcomes, 9,11 unilateral resection in patients with bilateral HS, even if the patient is rendered seizure-free, can compromise remaining memory function. 27,28 Moreover, ambulatory electrocorticography recorded from NeuroPace responsive neurostimulation devices has now shown that seizures may arise for several weeks in one hippocampus before then switching to the other. 29,30 Given that video-telemetry is typically of 1-2 weeks' duration, this may artificially skew interpretation if all, or most, of the seizures during EEG recording happen to arise from one of the sclerosed hippocampi.…”
Section: Discussionmentioning
confidence: 99%
“…Vogt et al (8) emphasized that despite further deficits in verbal memory, surgically treated BHS patients reported a slightly better subjective outcome than pharmacologically treated BHS patients did. Furthermore, this recent retrospective study carefully assessed neuropsychological outcome after epilepsy surgery in 11 patients with BHS, and reported that verbal memory further declined in 73% of the BHS patients, despite severe impairments already evident at baseline whereas nonverbal memory performance did not change significantly in any patient after surgery (8). We intriguingly showed that UHS and BHS groups did not show any significant difference even before surgery in almost all domains investigating nonverbal memory.…”
Section: Discussionmentioning
confidence: 99%